Assessment ranking for green pavement material elements - W. N. A., Wan Azahar; Putra Jaya, Ramadhansyah; M., Bujang; N., Kasim; N. N., Ismail; N. M., Husain; K., Basri; N. A. A. M., Hasazli (IOP Publishing, 2020)
The development of green roadway in Malaysia is one of the contributions to accomplish Malaysia Go Green Campaign. Hence, sustainable materials are widely used in road construction recently because people are more aware about its implications towards environments. However, people keep trying to find the most suitable sustainable materials to be used in designing road pavement. Hence, a new method is introduced which assessment ranking for green pavement material element and research is developed by finding and adding more green material used in designing pavements in Malaysia. They are then been categorized and analysed in order to identify which will become the most preferred material. Development of questionnaire survey is one of the steps involved as well as analysis of factor and ranking method for all the green material elements used in roads. About 25 respondents including teams from Public Work Department (JKR) and consultant company are chosen to answer the questionnaire survey according to their specialisation in road construction area. The agreement level which is the output from survey will be transferred into Minitab Software and measured using factor analysis. The factor score which is product from factor loading and mean values being restructure and becomes the weightage factor. Thus, all the material elements are ranked based on their weighted factor value. From the analysis of questionnaire survey, alternative binder become the most preferable material to be used for green pavement for it has the largest weighted factor.